2015
DOI: 10.1007/s10877-015-9787-3
|View full text |Cite
|
Sign up to set email alerts
|

Changes in intraocular pressure during surgery in the lateral decubitus position under sevoflurane and propofol anesthesia

Abstract: Intraocular pressure (IOP) has been shown to change with body position. Several studies have shown that the lateral decubitus position (LDP) is associated with a significant increase in IOP in the dependent eye. However, whether anesthetic agents alter IOP in the LDP remains unclear. This study investigated the effect of sevoflurane and propofol anesthesia on IOP in the LDP. A total of 28 patients undergoing surgery in the LDP were included. Patients were randomly allocated to sevoflurane or propofol groups. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 19 publications
(23 reference statements)
3
16
1
Order By: Relevance
“…[8] A few studies have evaluated IOP changes in patients undergoing general anesthesia in a lateral decubitus position. [9,14] Hwang et al reported that IOP of the dependent eye increased about 5 mm Hg from baseline by the end of the surgery in patients undergoing lung surgery under sevoflurane anesthesia. [14] Yamada et al compared the effects of sevoflurane and propofol on IOP and documented that IOP of the dependent eye increased approximately 8 mm Hg and 3.6 mm Hg from baseline with sevoflurane and propofol anesthesia, respectively, 1 hour after the position change to lateral decubitus.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[8] A few studies have evaluated IOP changes in patients undergoing general anesthesia in a lateral decubitus position. [9,14] Hwang et al reported that IOP of the dependent eye increased about 5 mm Hg from baseline by the end of the surgery in patients undergoing lung surgery under sevoflurane anesthesia. [14] Yamada et al compared the effects of sevoflurane and propofol on IOP and documented that IOP of the dependent eye increased approximately 8 mm Hg and 3.6 mm Hg from baseline with sevoflurane and propofol anesthesia, respectively, 1 hour after the position change to lateral decubitus.…”
Section: Discussionmentioning
confidence: 99%
“…Sample size calculation was performed with a power analysis based on data from a pilot study and previous study, [9] in which the mean IOP of the dependent eye in the lateral decubitus position in the propofol anesthesia group was 19.5 mm Hg compared with 23 mm Hg in the sevoflurane group. Power estimation analysis suggested that 21 patients per group would be required to detect a mean (± SD) difference in IOP of 3.5 ± 4 mm Hg with a power of 80%, considering a type I error of 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…19 Moreover, increase outflow of the aqueous humor could also contribute to the IOP decreasement. 20 Additionally, hemodynamic response associated with propofol could also reduce IOP at some degree. 7 In this study, both ipsi-operative and control-operative IOP at T2 (when TOF was below 0%) significantly decreased from the baseline values in all three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, the effect of inhalational sevoflurane anesthesia on lowering the intraocular pressure is already well known. 24,25 Data analysis was performed using the Statistical Package for Social Sciences SPSS for Windows version 20.0 (SPSS Inc., Chicago, IL, USA). Quantitative data were described using range, mean and standard deviation.…”
Section: Trabeculectomy Techniquementioning
confidence: 99%